Unexpected temperature dependence of 1H paramagnetic shift in MAS NMR of nickelocene - Xinbiao Jiang; Jiefan Liu; Xiaobing Lou; Bingwen Hu; Ming Shen (Magnetic Resonance Letters)
This work revisits the temperature dependence of 1H paramagnetic shift in nickelocene as a potential nuclear magnetic resonance (NMR) thermometer under fast magic angle spinning (MAS) rate. Surprisingly, an abnormal temperature dependence of 1H paramagnetic shift has been observed. In addition to a 1/T dependence term, a 1/T2 dependence term must be included to correctly describe the curvature behavior of the δ1H-T correlation under fast MAS rate.